2019
DOI: 10.1111/een.12801
|View full text |Cite
|
Sign up to set email alerts
|

Lack of prey switching and strong preference for mosquito prey by a temporary pond specialist predator

Abstract: 1. The strengths of trophic interactions within ecosystems can be mediated by complex mechanisms that require elucidation if researchers are to understand and predict population‐ and community‐level stabilities. Where multiple prey types co‐occur, prey switching (i.e. frequency‐dependent predation) by predators may facilitate low‐density prey refuge effects which promote coexistence. On the other hand, lack of switching and strong preferences by predators can strongly suppress prey populations, which is especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Some predators may shift prey preference according to the abundance of prey in the mixed prey system. The predator may have a disproportionately high predation on the most abundant prey and a disproportionately low predation on the rarer prey (Jaworski et al 2013, Cuthbert et al 2019b). In this study, although the nymph of T. turkestani and T. truncatus in size, mobility, and mechanism are similar, the available number of T. truncatus in the area was much less than T. turkestani .…”
Section: Discussionmentioning
confidence: 99%
“…Some predators may shift prey preference according to the abundance of prey in the mixed prey system. The predator may have a disproportionately high predation on the most abundant prey and a disproportionately low predation on the rarer prey (Jaworski et al 2013, Cuthbert et al 2019b). In this study, although the nymph of T. turkestani and T. truncatus in size, mobility, and mechanism are similar, the available number of T. truncatus in the area was much less than T. turkestani .…”
Section: Discussionmentioning
confidence: 99%
“…notonectids) colonise (Dalu et al, 2017b), and mosquito larval prey, which are known to externally colonise temporary aquatic systems. Previous research has demonstrated the potential role of mosquito prey in the diet of L. raynerae (Cuthbert et al, 2018b(Cuthbert et al, , 2019d. Specifically, we aim to decipher the effects of habitat structure and population sex demographics on biotic interactions, and whether the influence of habitat structure is dependent on the internal demographic characteristics within species.…”
Section: Introductionmentioning
confidence: 99%
“…If these ecosystems are compromised, such as through being deepened by land owners for water storage purposes, the potential for vector mosquito proliferation may increase. Whilst recent work has also demonstrated strong prey selectivity patterns by predators in temporary ponds (Cuthbert et al, 2019), future studies should also examine the influence of water volume on prey preferences in these systems to further elucidate the implications of search area for trophic interactions concerning vector mosquito populations. Field-based surveys to examine how culicid and daphnid prey abundances shift spatiotemporally according to pond characteristics are also warranted.…”
mentioning
confidence: 99%